2019
DOI: 10.1002/jcb.29120
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: New insights into cancer mechanisms

Abstract: Exosomes are mobile extracellular vesicles with a diameter 40 to 150 nm. They play a critical role in several processes such as the development of cancers, intercellular signaling, drug resistance mechanisms, and cell-to-cell communication by fusion onto the cell membrane of recipient cells. These vesicles contain endogenous proteins and both noncoding and coding RNAs (microRNA and messenger RNAs) that can be delivered to various types of cells. Furthermore, exosomes exist in body fluids such as plasma, cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 101 publications
0
30
0
Order By: Relevance
“…Specifically, the 15-LO-1/15-HETE system presents a potential approach for aiding neurobehavioral recovery after cerebral ischemic stroke, a beneficial effect mediated by upregulation of VEGF and subsequent promotion of angiogenesis in the ischemic brains [48]. Exosomal signaling during hypoxia regulates angiogenesis and migration of MECs [49], and recent research shows that hypoxia stimulates the release of exosomes in various tumor types, culminating in the activation of vascular cells and angiogenesis [50]. According to a recent review, cell-based and cell free (exosomes, extracellular vesicles, microRNAs) therapies have already been applied successfully for angiogenesis-mediated tissue regeneration and have great potential for treating ischemic heart disease, brain stroke, as well as bone defects [51].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the 15-LO-1/15-HETE system presents a potential approach for aiding neurobehavioral recovery after cerebral ischemic stroke, a beneficial effect mediated by upregulation of VEGF and subsequent promotion of angiogenesis in the ischemic brains [48]. Exosomal signaling during hypoxia regulates angiogenesis and migration of MECs [49], and recent research shows that hypoxia stimulates the release of exosomes in various tumor types, culminating in the activation of vascular cells and angiogenesis [50]. According to a recent review, cell-based and cell free (exosomes, extracellular vesicles, microRNAs) therapies have already been applied successfully for angiogenesis-mediated tissue regeneration and have great potential for treating ischemic heart disease, brain stroke, as well as bone defects [51].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the SYBR Green qPCR, the AllGlo qPCR method had a higher sensitivity and a wider linear range (10 3 -10 10 copies/µL), meaning that we could easily detect the miRNAs which were expressed in low abundance in the circulation. The levels of miRNAs in some body fluids such as urine, cerebrospinal fluid and exosome are much lower than those in serum or plasma, however studies had shown that they have great significance in the process of cancer development or some other diseases [33,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest with respect to GPR143 signaling is that L-DOPA stops exosome release in situ, suggesting that exosome release is controlled by at least one GPCR in the RPE-in this case, a GPCR tied to the pigmentation pathway. Significantly, this may well be the mechanism of action of L-DOPA in protection from AMD, since exosomes in other tissues and cancer cells drive angiogenesis through the miRNA cargo they carry [44,45]. In addition to a host of specific miRNA cargo, exosomes carry VEGF [46,47], which together can drive vascular cell proliferation and angiogenesis, indicating that exosomes may be stronger potentiators of angiogenesis than VEGF alone.…”
Section: Exosomesmentioning
confidence: 99%